Changes in physical activity behavior and development of cardiovascular risk in children. (11th May 2021) - Lona, G; Hauser, C; Koechli, S; Infanger, D; Endes, K; Faude, O; Hanssen, H
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Swiss National Foundation Background: Prevention of cardiovascular (CV) disease should start early in life. The study aimed to investigate the association of changes in physical activity, sedentary behavior and cardiorespiratory fitness (CRF) with development of body mass index (BMI), blood pressure (BP) and retinal microvascular health in children over four years. Methods: In 2014, 391 children aged 6-8 years were screened, and thereof 262 children were reexamined after four years following standardized protocols. Retinal arteriolar (CRAE) and venular diameters were measured by a retinal vessel analyzer. CRF was objectively assessed by a 20m shuttle run, physical activity and sedentary behavior by use of a questionnaire. Results: Children who achieved higher CRF levels reduced their BMI (β [95% CI] -0.35 [-0.46 to -0.25] kg/m2 per stage, P ≤ 0.001) and thereby developed wider CRAE (β [95% CI] 0.25 [0.24 to 0.48] µm per stage, P = 0.03) at follow-up. Moreover, children with elevated or high systolic BP at baseline, but lower levels of sedentary behavior during the observation period, had wider CRAE at follow-up (β [95% CI] -0.37 [-0.66 to -0.08] µm per 10 min/d, P = 0.013). Conclusion: An increase of CRF over four years was associated with a reduced BMI and consequently wider retinal arterioles at follow-up. In children with elevated or high systolic BP, a reduction of sedentary behavior by merely 10 min per day significantly improved retinal microvascular health as a primary prevention strategy to promote childhood health and combat development of manifest CV disease later in life.